2022
DOI: 10.17718/tojde.1182747
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Physics Teaching Materials in Blended Learning to Improve Self-Directed Learning Skills in Distance Education

Abstract: Atomic physics teaching materials support student motivation to learn independently, guide, and direct students to master material with abstract characteristics. The teaching materials in blended learning can improve the tutorial system’s interaction process in distance education with special characteristics. Universitas Terbuka students have various ages, professions, geographic location, social environment, and prior knowledge. This study aimed at analyzing the practicality and effectiveness of atomic physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(46 reference statements)
1
2
0
Order By: Relevance
“…The findings also indicate that the software was used actively as a shared resource to advance the joint enterprise, particularly in enabling the possibility to constantly share and (re-)use plans, provide feedback and support collaborative reflection. Earlier studies have documented that social media technology can support collaborative reflection and substantiate qualities associated with community of practice in practicum (Caner, 2010;Goktalay, 2015;Rutherford, 2010) -this study has confirmed these findings, and it has particularly shown that one particularly important potential the software could have for future practicum placements, is how it can strengthen the student teachers reflection through the process by a constant alternation between traditional (analogue) and digital collaborative activities (cf. Figure 3).…”
Section: The Potential Of Using the Technology To Support Reflection ...supporting
confidence: 77%
See 1 more Smart Citation
“…The findings also indicate that the software was used actively as a shared resource to advance the joint enterprise, particularly in enabling the possibility to constantly share and (re-)use plans, provide feedback and support collaborative reflection. Earlier studies have documented that social media technology can support collaborative reflection and substantiate qualities associated with community of practice in practicum (Caner, 2010;Goktalay, 2015;Rutherford, 2010) -this study has confirmed these findings, and it has particularly shown that one particularly important potential the software could have for future practicum placements, is how it can strengthen the student teachers reflection through the process by a constant alternation between traditional (analogue) and digital collaborative activities (cf. Figure 3).…”
Section: The Potential Of Using the Technology To Support Reflection ...supporting
confidence: 77%
“…In spite of the significant attention to and considerable testing of social media technology in many teacher education programmes in recent years, the empirical research documentation in the practicum context has been limited (Goktalay, 2015). All the same, it is indicated that social media can contribute to immediate feedback (Goktalay, 2015), more reflective practice (Hramiak et al, 2009), more committed, active and collaborative student teachers (Caner, 2010), and a stronger community of practice among peers, mentor teachers and university supervisors (Goktalay, 2015;Rutherford, 2010).…”
Section: Research On the Use Of Different Digital Modalities To Suppo...mentioning
confidence: 99%
“…Learning is carried out online with the online system. Even though it is carried out online, if appropriate teaching materials support learning in tutorial activities, it can improve students' independent learning outcomes (Erlina et al, 2022). Interactive teaching materials accompany the implementation of learning following the material presented, namely regarding various medicinal plants integrated according to local Balinese culture, Lontar Usada Taru Pramana.…”
Section: Resultsmentioning
confidence: 99%
“…The learning media for higher education students is designed for some scientific fields such as management (Li et al, 2020), English education (Amelia & Harmaini, 2020;Ramalingam et al, 2022)and theology (Stanislaus & Lee, 2021). Moreover, Erlina, Prayekti, and Wicaksono (2022) specifically studied the design of blended learning approach-based learning media for atomic physics course. Additionally, Musdalifah, Baharuddin, Jabri, Elihami, and Mustakim (2021) designed blended learning approachbased learning media for Islamic education course.…”
Section: Introductionmentioning
confidence: 99%